Make a Wish, Midas! - Holub, Joan; Patricelli, Leslie (New York : Abrams Appleseed, 2015)
Young Midas, who loves the color yellow, makes an impulsive wish that has dire consequences for his beloved toy dinosaur. Includes a retelling of the original Midas's Wish myth.
Keywords: Midas (Legendary character) -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Wishes -- Juvenile fiction; Midas (Legendary character) -- Fiction; Mythology, Greek -- Fiction; Wishes -- Fiction